Carol Gilligan’s hermeneutic method for ethics - Pereira, Viviane Magalhães (Argumentos - Revista de Filosofia, 2025)
This article aims to elucidate the method employed by the American philosopher Carol Gilligan to investigate ethics. It argues that her Listening Guide aligns with the assumptions of Hans-Georg Gadamer’s philosophical hermeneutics. By conducting her empirical research using this method, Gilligan contributes to addressing the contemporary problem of the grounding morality and to articulating a plausible ethical concept from a feminist perspective – namely that of responsible care.